Up-conversion and Tunable Up-conversion Emission from Nitrogen Functionalized Graphene Quantum Dots. Issue 1 (1st February 2022) - Siddique, A B; Prasad, K L V; Joseph, S M; Kishore, D; Das, B; Mubarak, S; Mukhuti, K; Ray, M
Abstract: In amidst of conflicts of opinion regarding the presence of up-conversion in carbonaceous nanostructure. We have critically and precisely asserted that there is a real up-conversion in the nitrogen functionalized graphene quantum dots (NGQDs), which is found to be its inherent feature and not a measurement artefact. We have demonstrated that NGQDs exhibit real up-conversion in the blue-green region. To define the perspective of the study a variant of GQDs, NGQDs was synthesized using facile, one-pot synthetic methods. We have critically examined the up-conversion emission in NGQDs, interestingly, N-GQDs exhibited very superior optical properties such as high quantum yield of 97%, up-conversion emission at 535 nm and tunable up-conversion that exhibited a red shift of 12 nm. The two-photon excitation process is the governing phenomenon behind the real up-conversion in NGQDs which is suggested by the quadratic dependence of the integrated intensity on excitation power. Up-conversion can enhance the efficiency of the photovoltaic solar cell by even converting infrared region of sunlight to electricity. Moreover, tunable up-conversion open the door for promising applications of NGQDs in tunable fibre lasers, multicolour displays and multiphoton optical data storage.